(3ddhMj eYGf CNQis (3gd GdhMj CeQ eecf YbdjG?s - (3GdNTJ, eMeO YKeGfs ((3GdbGgQIs (3GdgjFI GdYGeI dbUhQ GdKbGaIs, 2013)
(3JhLO GNJdGaGJ Hjf GdCOjGf aj WHjYI GdhMj hhSGFdg , ceG JhLO CTcGd eJfhYI ddhMj , efgG CSdhH GdhMj aj GdJbdjO GdjghOj (B- (3GdeSjMj (B- (3GdESdGej , hgfGc GNJdGaGJ djSJ HGdbdjdI Hjf GdOjGfGJ GdEHQGgjejI GdJj JfJej Edi eSGQ hGMO ef MjK GdfTCI , dcfgG GJNPJ CKfGA fehgG hJLdjgG aj GdJGQjN WHGFY eNJdaI JUd CMjGfG Edi MO GdJYGQV(B. (3hJbOe HYV GdCOjGf GdCNQi aj EWGQ eNJda JYGdjegG chMj SeGhj , EdG CfgG JfSH CeQ JSdjegG Edi eDSS CSWhQj Ch NQGaj cgQeS GdPj JfSH Edjg eLehYI GdJYGdje GdOjfjI hGdadSajI GdSQjI(B. (3hjgOa gPG GdHMK Edi cTa GddKGe Yf ChLg GdJTGHg hGdGNJdGa HjfgG , eY HjGf GdJCSjS GdadSaj hGdETQGbj ddfHhI ; ddcTa Yf WHjYI CfeGW GdhMj aj VhA efgL JMdjdj ebGQf ddfUhUs
11
Keywords: (3GdCfHjGAs; (3GdhMjs -- (3GdfHhIs